Pengaruh Penerapan Metode Pembelajaran Everyone is a Teacher Here terhadap Minat dan Hasil Belajar Matematika Materi Pecahan di Madrasah Ibtidaiah - Hikmah, Dewi Wahyuning; Septiani, Putri (IBTIDA', 2022)
The purpose of this study was to find out whether by applying the Everyone is teacher here learning method, there was an increase in the learning interest of fourth graders in the Mathematics subject matter of fractions at MI Tanwirul Mubtadiin Pendil-Banyuanyar. The method used in this research is classroom action research method. Data collection techniques used are observation, interviews, tests, and documentation. Based on research that has been carried out in class IV MI Tanwirul Mubtadiin and from the analysis of the data, it can be concluded that through the learning method everyone is teacher here can increase student interest and learning outcomes. This is indicated by the increasing average mathematical reasoning ability and student interest from pre-cycle 40 to 65.71 in cycle 1 and increased to 88.57 in cycle 2. Likewise, students' interest in learning which was originally with a percentage of 52.04% in cycle 1 to 85.71% in cycle 2.